Neotectonic architecture of Taiwan and its implications for future large earthquakes - Shyu, J. Bruce H. (2012)
The disastrous effects of the 1999 Chi-Chi earthquake in Taiwan demonstrated an urgent need for better knowledge of the island's potential earthquake sources. Toward this end, we have prepared a neotectonic map of Taiwan. The map and related cross sections are based upon structural and geomorphic expression of active faults and folds both in the field and on shaded relief maps prepared from a 40-m resolution digital elevation model, augmented by geodetic and seismologic data. The active tandem suturing and tandem disengagement of a volcanic arc and a continental sliver to and from the Eurasian continental margin have created two neotectonic belts in Taiwan. In the southern part of the orogen both belts are in the final stage of consuming oceanic crust. Collision and suturing occur in the middle part of both belts, and postcollisional collapse and extension dominate the island's northern and northeastern flanks. Both belts consist of several distinct neotectonic domains. Seven domains (Kaoping, Chiayi, Taichung, Miaoli, Hsinchu, Ilan, and Taipei) constitute the western belt, and four domains (Lutao-Lanyu, Taitung, Hualien, and Ryukyu) make up the eastern belt. Each domain is defined by a distinct suite of active structures. For example, the Chelungpu fault (source of the 1999 earthquake) and its western neighbor, the Changhua fault, are the principal components of the Taichung Domain, whereas both its neighboring domains, the Chiayi and Miaoli Domains, are dominated by major blind faults. In most of the domains the size of the principal active fault is large enough to produce future earthquakes with magnitudes in the mid-7 values.